Orbital dermoids: clinical presentation and management. Issue 9 (September 1984) - Sherman, R P; Rootman, J; Lapointe, J S
Abstract : The authors have reviewed 15 cases of orbital dermoids representing 6% of orbital tumours seen at the University of British Columbia Orbital Clinic. They tended to occur as either asymptomatic superficial lesions in children or as complicated deep lesions in adolescents and adults. The superficial lesions were as frequent medially as laterally and could be dealt with by a direct uncomplicated surgical approach. The deep lesions in contrast, were frequently extensive and difficult to remove, requiring careful preoperative planning. Sites of origin, presentation, differential diagnosis, and management are discussed.